The business suit: transitional phenomena and religious comparison - Seales, Chad (Religion, 2025)
This article invokes the analytical concept of transitional phenomena, as inspired by the psychoanalytical theories of Donald Winnicott, to develop a materialist model for comparing religion. Transitional phenomena are persons, places, or things that mediate material reality and discursive representation. The article focuses on the case study of the business suit at the 1893 World’s Parliament of Religions to show how the psychological duality of transitional phenomena in the creative construction of ‘me’ and ‘not-me’ is related to material and spatial distinctions in the discursive invention of ‘religion’ and ‘not-religion’. The goal of the issue is to show how the comparison of religion is not just a discursive problem of defining categories and classifying accordingly. Rather, it requires attending to the materialist connections between the categories of religious comparison and the social order of persons, places, and things that generate the possibility of comparison.